Identifying Children and Youth With Autism Spectrum Disorder in Electronic Medical Records: Examining Health System Utilization and Comorbidities. Issue 2 (24th October 2020) - Brooks, Jennifer D.; Bronskill, Susan E.; Fu, Longdi; Saxena, Farah E.; Arneja, Jasleen; Pinzaru, Virgiliu Bogdan; Anagnostou, Evdokia; Nylen, Kirk; McLaughlin, John; Tu, Karen
Abstract : Autism spectrum disorder (ASD) is a neurodevelopmental disorder requiring significant health and educational resources for affected individuals. A reference standard for ASD was generated from an existing population‐based cohort of 10, 000 children and youth aged 1–24 years who were randomly selected for chart abstraction from 29, 256 patients from 119 family physicians. We developed and validated an algorithm to identify children and youth with ASD within an electronic medical record system ( N = 80, 237, aged 1–24 years) in order to examine the prevalence of comorbidities and quantify health system utilization within the cohort. We identified 1, 062 children and youth with ASD representing a prevalence of 1.32%. Compared to individuals without ASD, those with ASD had a higher prevalence of asthma, were more likely to visit a specialist, undergo surgery, and be hospitalized for psychiatric reasons. Children and youth with ASD in Ontario have complex health system needs, illustrated through a significant burden of comorbidities and increased health system utilization. Lay Summary: Our paper generates population‐based estimates of health system use by children and youth with ASD, who have a higher burden of comorbidities than the general population. We developed a case‐finding algorithm and applied it in electronic medical records to create a cohort of children and youth with ASD, thereby generating an important resource to further study the health care needs of individuals with ASD.